Wall Pressure and Blade Surface Pressure in a Side Channel Blower - Sven Münsterjohann; Stefan Becker (International Journal of Rotating Machinery)
In side channel blowers, the pressure field is the result of complex, inner flow mechanisms. While there are already experimental investigations on the wall pressure distributions, little is known about the pressure in the rotating system, i.e., on the blade surface. In this work, we present an experimental setup for measuring the unsteady blade surface pressure in several positions. The acquired data will be complemented by and compared to the additionally measured wall pressure on the side channel housing. Miniature pressure sensors are integrated into the impeller. It is modified to ensure flush mounted membranes of the sensors and to avoid impacting on the flow field. A telemetric system is used for a wireless transfer of the data from the rotating system to the data recorder. As a result, we show the time-resolved pressure distribution as well as its phase-locked ensemble average. The variations of the pressure field are related to the integral pressure difference across the turbomachine and to its rotational speed. Due to the high temporal resolution of the measurement data, an exact spatial localization of crucial flow phenomena is achieved. Low integral pressure differences show a nearly linear increase of the pressure in circumferential direction, while greater integral pressure differences evolve exponentially over the azimuth. The results confirm the circulatory flow theory. Different rotational speeds elicit a comparable behavior. The stripper is a dominant source for pressure fluctuations. Its individual geometric discontinuities are correlated to the flow field. Our results provide a deeper understanding of the flow phenomena in side channel blowers and the theory of pressure generation. Although the measurements were performed for only one type of side channel blower with a double-flow configuration and open blades, the energy transfer mechanism is the same for other modifications like single flow or closed blade versions.